Objectives Key Results Perusahaan Modest Fashion Islami: Analisis Kritis Berdasarkan Konsep Maslahah - Rendi Emalia; M. Nur A. Birton; M. Irfan Tarmizi (Universitas Muhammadiyah Jakarta, 2026)
Objectives: This study aims to analyze performance measurement using Objectives and Key Results (OKR), and critically examine the implementation of OKR through Jasser Auda’s concept of maslahah in an Islamic fashion company. Design/method/approach: This study employed a qualitative approach within an Islamic paradigm. Data were collected through in-depth interviews, participant observation, and document analysis involving nine informants, comprising three chief officers, five heads of department, and one cost accounting manager. Data were analyzed qualitatively using the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing/verification. The implementation of Objectives and Key Results (OKR) was further analyzed using Jasser Auda's six features of maslahahh to evaluate its effectiveness as an adaptive, holistic, and maslahah-oriented performance measurement system. Results/findings: The implementation of OKR has not yet resolved the issue of high inventory levels because the findings were not synchronized with key results and key initiatives. Moreover, the existing OKR framework has not yet aligned with the six features of maslahah. Theoretical contribution: This study extends contemporary performance measurement discourse from an Islamic values perspective. Practical contribution: The findings encourage the design of more adaptive, aligned, and maslahah-oriented OKR systems. Limitations: The study is limited to evaluating the implementation of Objectives and Key Results (OKR) and inventory-level issues. The impact of OKR on other performance dimensions, such as employee productivity, customer satisfaction, and organizational sustainability, has not been examined in depth.